The Relationships of Cytomegalovirus’s Infection among Pregnant Women with Some Variables - Saadya Hadi Humade (Journal of Global Pharma Technology, 2018)
Back ground: CMV is Human Herpesvirus 5 (HHV-5). Belong to the ''Betaherpesvirinae'' subfamily of ''Herpesviridae'', which also includes Roseola virus. It leads to an initial CMV infection, with a few symptoms. The virus remains latent in the body, reactivating when the body’s immune system is weakened. CMV causes an estimated 400 deaths each year and permanent disabilities in about 8,000 children, according to statistics by the U.S. Centers for Disease Control and Prevention. A pregnant woman can pass CMV to her child and the results gave birth has severe cerebral palsy, hearing and vision loss. Treating a pregnant woman for CMV will lessen or prevent long term disabilities of the fetus in utero. Objective: To find out the relationship between demographic variable and reproductive variable with the predisposing factors of the disease. Methodology: descriptive study done at Bable maternity hospital conducted, a purposive sample of (56) women how have Cytomegalovirus, from the period 1/4/2017 to 30/4/2017. Results: the study revealed that the high percentage for women who affected with CMV with in age group (16-25) years (41.1%). (33.9%) graduated from the primary school related reproductive variable,(94.28%) they have number (1-4) graveda, (92.8%) they have(92.8%)they have (1-4) para and (76.78%) they have(1-3) abortion.(78.6%) they aborted at 11-20 weeks gestation. Also (30.4%) they have fetal anomalies and (50%)at they didn’t taking medication during pregnancy. The study revealed that a highly significant correlation between age and education, occupation, residence, gravida, para and abortion, highly significant correlation between Gestational age and fetal anomalies and immune disease and highly significant correlation between fetal anomalies& immune disease. Conclusion: the study was concluded that the study sample don’t aware about CMV and its complication. Recommendation: Sequential ultrasound examinations should be performed every 2 to 4 weeks to detect sonographic abnormalities, to determine the prediction of the fetus and serologic testing for CMV for women who develop influenza-like illness during pregnancy.Keywords: Cytomegalovirus, fetal anomalies, abortion.